Pengaruh Penerapan Anggaran Berbasis Kinerja, Kompetensi Sumber Daya Manusia Dan Disiplin Pegawai Terhadap Kinerja Aparatur Pengelola Keuangan Pada Satuan Kerja Perangkat Daerah (SKPD) Pemerintah Kota Banda Aceh - Juraida Juraida; Ridwan Ridwan (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine the effect of the implementation of performance-based budgeting, human resource competencies and staff’s discipline towards the financial performance of the apparatus manager (either simultaneously or partially) on the regional work units (SKPD) Government of Banda Aceh. The population in this study were the apparatus SKPD that play role in financial management consisting of Budget Users (PA), Financial Administration Officer (PPK) and treasurer of 38 SKPD in Government of Banda Aceh with  total population of 114 people. The analytical method used in this study was multiple linear regression. This study used primary data, from respondents' answers to the questionnaire statement. The results showed that the implementation of performance-based budgeting, human resources competencies and employee discipline either simultaneously or partially affected the performance of the apparatus of financial management at SKPD Government of Banda Aceh.KEYWORDS : Performance-based Budgeting, Human Resources Competency, Employee Discipline and Performance Financial Management Apparatus